Perceived Stigmatization in Iranian Children With Deformities or Scars Caused by Burns Referred to Treatment Centers in Tehran, Iran - Mahboobe Aliakbari; Mahnaz Shoghi; Fatemeh Rahimi Nasrabadi (Iran University of Medical Sciences, 2024)
Background & Aims Experiencing stigmatization behaviors in children with post-burn deformities  can leave lasting negative effects on their mental and social health, and is considered an important issue in the child's growth and development. This research aims to investigate the perceived stigmatization in children with deformities or visible scars caused by burns referred to treatment centers in Tehran, Iran. Materials & Methods In this cross-sectional study, 190 children aged 8-18 years with a history of burns resulted in deformities or visible scars participated. Sampling was done using a convenience method from October 20, 2021, to October 20, 2022. The 21-item perceived stigmatization questionnaire (PSQ) was used to collect information. Data analysis was performed in SPSS software, version 21 using independent T-tests and analysis of variance. Results The mean total score of PSQ was 2.199 ± 0.562. The domain of confusing/staring behaviors had the highest score of 2.517±0.820. Perceived stigmatization showed significant relationships with children's age (P=0.030), gender (P= 0.010), educational level (P< 0.001), time since burn (P<0.001), and frequency of reconstructive burn surgery (P=0.009). Moreover, perceived stigma in children was significantly correlated with their mothers' education level (P=0.007) and occupation (P=0.003). Conclusion Female children with deformities or visible scars caused by burns tend to experience stigmatization behaviors more frequently than males. These children experience these behaviors mostly during early adolescence. Additionally, a higher number of reconstructive surgeries and a shorter time since the burn accident are linked to high perception of stigmatization in these children. Moreover, children of employed mothers and those whose mothers have higher educational levels report more perceived stigmatization. It is important for nurses to identify these issues and refer the cases who require additional support to available social treatment centers for further assistance.